Assessing an acoustic bioindicator of leisure boating disturbance on bottlenose dolphins - Gabriella La Manna; Fabio Ronchetti; Francesco Perretti; Giulia Ceccherelli (PeerJ, 2025)
Growing concerns about the impact of leisure boating on marine ecosystems are particularly relevant for marine mammal species, given their dependence on sound and significant spatial overlap with human activities. Monitoring the effects of leisure boating disturbances on marine ecosystems presents considerable challenges, as it is resource-intensive and may require many years of data collection. However, since species can alter their behavior and daily routines in response to human disturbances, behaviors essential for individual fitness, reproduction, and parental care success—such as acoustic behavior—could serve as bioindicators for assessing the impact of leisure boating. Common bottlenose dolphins (Tursiops truncatus) emit acoustic signals, known as signature whistles (SWs), for individual identification, communication, and social bonding. This study aimed to examine how leisure boating influences SW characteristics (e.g., fundamental frequencies, frequency modulation, and duration) and whether these effects remain consistent across different social contexts (e.g., presence of calves), environmental conditions (e.g., seabed habitat type), and behavioral states in a population of bottlenose dolphins inhabiting the northwestern coast of Sardinia (Mediterranean Sea, Italy). The results demonstrate that certain SW characteristics were consistently affected by the presence of boats, regardless of ecological, behavioral, and social differences. These findings suggest that SWs have the potential to serve as reliable bioindicators for boating disturbances. Further research in diverse marine environments and with other dolphin populations is needed to validate and expand upon these findings.